IDNLearn.com: Where your questions meet expert advice and community support. Ask anything and receive immediate, well-informed answers from our dedicated community of experts.
Sagot :
Answer:
Step-by-step explanation:
By the Pythagorean Theorem
[tex]c^2=a^2+b^2\\ \\ c^2=60^2+32^2\\ \\ c^2=4624\\ \\ x=\sqrt{4624}\\ \\ x=68[/tex]
use the pythagorean theorem to figure this out:
a^2 + b^2 = c^2
plug in the values:
60^2 + 32^2 = x^2
simplify:
3600 + 1024 = x^2
4624 = x^2
√4624 = x
68 = x
the answer is x = 68
a^2 + b^2 = c^2
plug in the values:
60^2 + 32^2 = x^2
simplify:
3600 + 1024 = x^2
4624 = x^2
√4624 = x
68 = x
the answer is x = 68
Thank you for using this platform to share and learn. Keep asking and answering. We appreciate every contribution you make. Accurate answers are just a click away at IDNLearn.com. Thanks for stopping by, and come back for more reliable solutions.